PENGEMBANGAN APLIKASI ANDROID UNTUK PEMBELAJARAN MOBILE LEARNING PADA POKOK BAHASAN ALAT-ALAT OPTIK - Ruhiyat Rizki Permana; Supriyadi A.; Handjoko Permana; Ghina Afifa Ishak; Widyanirmala Widyanirmala; Nur Azizah; Aditiya Nugraha (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
The aim of this research is to develop a mobile learning instructional media android application on the subject of optical instruments. This application contains material learning across levels of education on the same subject, namely: optical instruments (SMA), reflection and refraction (SMP) and light (SD). The research was conducted between January and July 2013 in the Digital Media Laboratory of Physics, State University of Jakarta, and tested in SMA 30 and SMA Negeri Jakarta Pusat Jakarta Selatan 38 to 30 students as a learning object. The method used in this research is the development of research methods (Research and Development). With the design phase of products, product development, product testing and product revision. The results of this study are in the form of Android-based learning application that is used as a medium of learning support at school physics. This learning application has been validated by 2 people matter experts with an average percentage of 91.67%, 2 media expert with an average percentage of 80.96%, and 2 high school physics teacher with an average percentage of 81.81%. This learning application has also been through a process of trial is limited to 10 students and a small group of trials to 20 students, with an average percentage of 82.03%. These results indicate that the android app for learning mobile learning have been fit for use as a medium of learning support at school physics. Keywords: Development, Application Learning, Mobile Learning.